Algoritmization of integer polynomials and deduction of formulas for calculations of the sums of their products - Šukys, Algirdas (Lietuvos matematikos rinkinys, 1997)
The article deals with an algorithm of deducing such formulas that make easy their realization by computer. The formulas deduced can be applied in calculus, algebra, analysis of indefinite sums and in mathematical statistics.